Interactive Teaching and Learning Techniques - Karki, Manita (Journal of NELTA, 2018)
Many teachers still follow the traditional method of lecturing to teach English as a foreign language rather than making students actively engage in learning processes. This lesson focuses on different activities to engage beginners actively to learn English language.